Living with Overtourism: Community Narratives of Cultural, Environmental, and Social Change in Bali, Indonesia - Pramuja, Risky Angga (Advances in Tourism Studies, 2024)
Overtourism has become a pressing concern in Bali, where rapid tourist growth has generated cultural, environmental, and social tensions. While much of the literature emphasizes visitor management and economic implications, less is known about how local residents themselves interpret and respond to these dynamics. This qualitative study explores community narratives of overtourism in three high-density tourism areas: Ubud, Kuta, and Canggu. Using in-depth interviews and focus group discussions with residents, cultural practitioners, and community leaders, the research examines how everyday life is shaped by issues of crowding, cultural commodification, environmental stress, and shifting power relations between locals and external actors. Thematic analysis reveals that residents perceive overtourism not only as a source of economic opportunity but also as a threat to cultural integrity, social cohesion, and ecological sustainability. At the same time, communities articulate diverse coping strategies, ranging from informal regulation of tourist behaviors to the reinvention of local practices for new markets. The findings contribute to critical debates on sustainable tourism by foregrounding community perspectives, offering nuanced insights into how overtourism is lived, contested, and negotiated in a major Southeast Asian destination.